Modelling of filtration and heat and mass transfer processes in groundwater: applied aspects - Bubnova, O. A.; Miroshnyk, V. A.; Markul, R. V.; Mashykhina, P. B.; Berlov, O. V. (Science and Transport Progress, 2025)
Purpose. Liquid waste disposal is an urgent problem in many countries around the world. The most widely used method of liquid waste disposal is the creation of sedimentation ponds. However, this approach takes a significant amount of land out of use and, in combination with intensive pollution of the aeration zone and groundwater, is widely used for water supply in rural areas. Therefore, alternative methods of liquid waste disposal are constantly being sought for each specific region. One of the ways to dispose of liquid waste that is often used, in particular abroad, is underground disposal. This approach can be very effective and environmentally friendly if there are suitable hydrological conditions in the region, namely deep underground horizons containing substandard groundwater. This approach requires the use of specialised mathematical models. The aim of this study is to develop fast-calculating mathematical models for assessing the impact of underground disposal of liquid wastewater on groundwater pollution. Methodology. The mass transfer equation is used to solve the problems of mass transfer of impurities in the underground aquifer. A planned filtration model is used to model groundwater dynamics. A two-dimensional mass transfer equation is used to describe the geomigration process. The process of thermal contamination of groundwater is modeled on the basis of the energy equation. An explicit difference scheme is used to numerically integrate the filtration equation. Numerical integration of the modeling equation of mass transfer and energy is carried out on the basis of a variable-triangular splitting scheme. Findings. The development of mathematical models of heat and mass transfer, which allow to estimate the dynamics of changes in the groundwater regime and heat and mass transfer processes during underground disposal of liquid waste, is considered. Originality. The article considers the development of numerical models for analyzing the impact of underground disposal of liquid waste on groundwater. Numerical models take into account the convective-diffusion process of impurity propagation and changes in the thermal regime in groundwater. Practical value. The considered mathematical models can be used in the design of underground liquid waste disposal systems.